PERGESERAN NILAI TRADISI REBO PUNGKASAN PADA MASYARAKAT JAWA PERANTAUAN DI KELURAHAN SRIDADI, KECAMATAN MUARA BULIAN - Ratri, Ratri Yulia Ningsih; Melisa; Nurmalia Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study focuses on the shift in values surrounding the Rebo Pungkasan tradition among Javanese migrants in Sridadi Urban Village, Muara Bulian District. The main issues addressed are the transformation in how the tradition is carried out, the declining understanding of its meaning, and reduced community participation—particularly among the younger generation. These changes have contributed to the erosion of the tradition’s social, spiritual, and cultural identity. The objective of this research is to identify the factors influencing the shift in values and the efforts made to preserve the core values of the Rebo Pungkasan tradition. This research employs a descriptive qualitative method, with data collected through in-depth interviews, participant observation, and documentation. The findings reveal that value shifts are driven by factors such as globalization, modernization, cultural openness, socio-economic conditions, and increasing heterogeneity within the community. These influences have led to adjustments in the timing of the tradition, simplification of activities, and a decrease in youth involvement. Despite these challenges, the community continues to show commitment to preserving core values like spirituality, solidarity, and mutual cooperation. Preservation efforts include engaging community leaders, fostering intergenerational transmission, promoting the tradition through social media, and maintaining a selective approach to external influences. Consensus-based decision-making and cultural adaptation have become key strategies in ensuring that Rebo Pungkasan remains a meaningful part of the spiritual and social identity of the Javanese diaspora in Sridadi.